Assessment Design and Analysis of Arabic Reading Skills Instructional Materials - Zakkiyah, Maulia Yasminah; Fidyahwati, Nurriya Maghfirah; Ma'suq, Ahmad Tarajjil; Anggraini, Novita (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
Instructional materials play a vital role in learning, with assessment design being crucial for evaluating learning outcomes. This article focuses on the assessment design of reading skills instructional materials through test instruments and their analysis using surveys. The study employs a qualitative literature review approach, utilizing documentation study techniques for data collection and enhanced diligence in analysis. Test instruments are essential for evaluating students' abilities, hinging on validity, reliability, practicality, discrimination, and objectivity. Language tests vary based on test-taking methods, answer formats, and assessment methods while reading skills encompass mechanical, comprehension, and extensive aspects. The criteria for test instruments include reliability, validity, practicality, discrimination, and objectivity, with design steps involving goal setting, material selection, question development, difficulty level adjustment, testing, evaluation, and result utilization. Survey-based analysis evaluates content, presentation, language, readability, graphics, and production, considering relevance, sufficiency, accuracy, proportionality, readability, and graphic quality. Well-designed instruments and materials can significantly enhance Arabic reading skills.